Прогностическая значимость элевации нейроиммунных маркеров у больных с эссенциальной артериальной гипертензией и последствиями инфаркта мозга - Визир, В.А.; Волошина, И.Н. (Таврический медико-биологический вестник, 2012)
В дослідженні проведено визначення сироваткового вмісту інтерлейкіну-17 і антитіл до NR2- пептиду у пацієнтів з гіпертонічною хворобою III стадіїз наслідкамиінфаркту мозку, встановлено прогностичну значущість цих аутоімуних маркерів для розвитку церебро- і кардіоваскулярних ускладнень. The evaluation of serum interleukin-17 level and quantity measurements of antibodies to NR2-peptide in post-stroke hypertensive patients has been done. It has been established that the quantity of antibodies to NR2-peptide hasa strong predictive value for cardiovascular complications and recurrent stroke.